Ligand-dependent stereoselective Suzuki-Miyaura cross-coupling reactions of β-enamido triflates - Chvojka, Tomáš; Markos, Athanasios; Voltrová, Svatava; Pohl, Radek; Beier, Petr (Beilstein journal of organic chemistry, 2021)
The stereoselective Suzuki-Miyaura cross-coupling of (Z)-β-enamido triflates is demonstrated. Depending on the nature of the ligand in the palladium catalyst, either retention or inversion of the configuration during the synthesis of β,β-diaryl-substituted enamides is observed. Thus, the method provides synthetic access to both isomers of the target enamides from (Z)-β-enamido triflates.
Keywords: isomerization; enamides; Suzuki–Miyaura coupling; vinyl triflates